2013
DOI: 10.1007/s10339-013-0589-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotion words and categories: evidence from lexical decision

Abstract: We examined the categorical nature of emotion word recognition. Positive, negative, and neutral words were presented in lexical decision tasks. Word frequency was additionally manipulated. In Experiment 1, "positive" and "negative" categories of words were implicitly indicated by the blocked design employed. A significant emotion-frequency interaction was obtained, replicating past research. While positive words consistently elicited faster responses than neutral words, only low frequency negative words demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…Again, the results of several studies underline the importance of controlling word frequency effects in studies dealing with the processing of emotional words. Along these lines, interactions between word frequency and valence have been observed, especially during the processing of lowfrequency negative words (Méndez-Bértolo et al, 2011b;Scott, O'Donnell, Leuthold, & Sereno, 2009;Scott, O'Donnell, & Sereno, 2014).…”
Section: Relationship Between Affective and Psycholinguistic Variablesmentioning
confidence: 92%
“…Again, the results of several studies underline the importance of controlling word frequency effects in studies dealing with the processing of emotional words. Along these lines, interactions between word frequency and valence have been observed, especially during the processing of lowfrequency negative words (Méndez-Bértolo et al, 2011b;Scott, O'Donnell, Leuthold, & Sereno, 2009;Scott, O'Donnell, & Sereno, 2014).…”
Section: Relationship Between Affective and Psycholinguistic Variablesmentioning
confidence: 92%
“…A significant number of studies have revealed that these effects are pervasive. Indeed, modulations of the processing of words by their emotional content have been documented not only in tasks involving affective decisions (Estes & Verges, 2008;González-Villar, Triñanes, Zurrón, & Carrillo-de-la-Peña, 2014;Herbert, Kissler, Junghöfer, Peyk, & Rockstroh, 2006), but also in experimental situations in which the emotional content was irrelevant to the task (González-Villar et al, 2014;Hinojosa, Méndez-Bértolo, & Pozo, 2010;Kousta, Vinson, & Vigliocco 2009;Schacht & Sommer, 2009;Scott, O'Donnell, & Sereno 2014).…”
mentioning
confidence: 99%
“…In the psycholinguistic literature, emotion is generally represented within a two-dimensional framework (e.g., Osgood, Suci, & Tannenbaum, 1957;Russell, 1980), with greater emotionality associated with higher arousal and extreme valence. In behavioral terms, positive and negative emotion words tend to be recognized faster than comparable neutral words (e.g., Scott et al, 2009Scott et al, , 2012Scott et al, , 2014Sereno et al, 2015;Yao et al, 2017).…”
Section: Dimension(s)mentioning
confidence: 99%